Single-Cell RNA Sequencing Reveals Cellular and Transcriptional Changes Associated With Traumatic Brain Injury - Xing, Jin; Ren, Li; Xu, Hao; Zhao, Liang; Wang, Zhi-Han; Hu, Guang-Dong; Wei, Zi-Long (Frontiers in Genetics, 2022)
Traumatic brain injury (TBI) is currently a substantial public health problem and one of the leading causes of morbidity and mortality worldwide. However, the cellular and transcriptional changes in TBI at single-cell level have not been well characterized. In this study, we reanalyzed a single-cell RNA sequencing (scRNA-seq) dataset of mouse hippocampus to identify the key cellular and transcriptional changes associated with TBI. Specifically, we found that oligodendrocytes were the most abundant cell type in mouse hippocampus, and detected an expanded astrocyte population, which was significantly activated in TBI. The enhanced activity of inflammatory response-related pathways in the astrocytes of TBI samples suggested that the astrocytes, along with microglia, which were the major brain-resident immune cells, were responsible for inflammation in the acute phase of TBI. Hormone secretion, transport, and exocytosis were found upregulated in the excitatory neurons of TBI, which gave us a hint that excitatory neurons might excessively transport and excrete glutamate in response to TBI. Moreover, the ependymal subpopulation C0 was TBI-specific and characterized by downregulated cilium movement, indicating that the attenuated activity of cilium movement following TBI might decrease cerebrospinal fluid flow. Furthermore, we observed that downregulated genes in response to candesartan treatment were preferentially expressed in excitatory neurons and were related to pathways like neuronal systems and neuroactive ligand-receptor interaction, indicating that candesartan might promote recovery of neurons after traumatic brain injury via mediating neuroactive ligand-receptor interactions and reducing excitotoxicity. In conclusion, our study identified key cell types in TBI, which improved our understanding of the cellular and transcriptional changes after TBI and offered an insight into the molecular mechanisms that could serve as therapeutic targets.